Transformational and narcissist leaders: Their different behaviors in different contexts. (June 2022) - Jackson, Chris J.; Roberts, Jonathan
Abstract: Transformational and narcissist leaders are both typified as charismatic, yet little is known about how contextual factors moderate their workplace behavior. Drawing on Weber's classic theory of charismatic authority, this experimental study ( n  = 385 managers) used scenarios to investigate how job security and accountability moderated transformational leadership and narcissism of leaders in the prediction of intended charismatic rhetoric and risk-taking. In support of Weber's theory, transformational leaders intended to take risks in low job security and low accountability. In contrast, narcissist leaders intended to take risks in high job security and high accountability. Both transformational and narcissist leaders intended to engage in charismatic rhetoric across all contexts. It is concluded that intentions to engage in risk-taking in different contexts will differentiate the transformational leader from the narcissist leader. Selection implications are discussed.